Plasmonic Interaction in Enhanced Luminescent Down-Shifting Layers for Photovoltaic Devices - Ahmed, Hind; Mc Cormack, Sarah (Nova Science Publishers, 2017)
Harvesting solar energy has the potential to reduce carbon emissions and to provide clean energy contributing to sustainable development. Most photovoltaic (PV) research to date has focused on achieving higher PV conversion efficiency at lower cost. However, spectral losses due to limited spectral response of solar cells represent a fundamental limit to the maximum efficiency achievable by the single p-n junction solar cells. Low energy photons are not absorbed by the solar cell, while high energy photons are not used efficiently and energy is lost via thermalization. The potential exists to increase the solar cell efficiency bymaking better use of short wavelength light. One way to do this is to use a luminescent material to convert high energy photons to lower energy photons before the interaction with the solar cells occurs, a process referred to as luminescent down shifting (LDS). LDS suffers from self-absorption which undermines the efficiency of the LDS device. The downshifted photons are re-absorbed by the material within the down shifting layer which is a function of optical path length, concentration, and Stokes shift. A novel approach was proposed to utilize metal nanoparticles with the objective of counteracting these optical loss mechanisms (Ahmed, 2015, Ahmed, et al., 2016a). Plasmonic Luminescent Down-Shifting (pLDS) is a new optical approach to increase a PV deviceefficiency by using plasmonic coupling between luminescent materials and metal nanoparticles (MNP). The optical properties of fluorescent species can exhibit dramatic spectral changes in the presence of metal nanoparticles. In this chapter, luminescent materials suitable for incorporation in LDS layers are described. A literature review on solar cell optical response and efficiencies is presented and plasmonic interaction of metal nanoparticles is discussed. Fabricated pLDS devices are presented along with their optical and electrical characterization. The results have shown significant enhancement in absorption, fluorescence emission and electrical output of the plasmonic photovoltaic devices
Plasmonics: Advances in Research and Application.
PUBLISHED
USA
Keywords: Spectral losses; Photovoltaics; Luminescent materials; Plasmonic luminescent down-shifting layers; Creative Technologies; Nanoscience & Materials; Education